Receptorial and mitochondrial apoptotic pathways in normal and neoplastic human endometrium. Issue 3 (1st April 2005) - Di Paola, M.; Loverro, G.; Caringella, A. M.; Cormio, G.; Selvaggi, L.
Abstract : Under normal conditions, in human endometrium, apoptotic and antiapoptotic factors play an important role in tissue homeostasis. Abnormalities of apoptosis, a process implicated in several events in the reproductive organs, may contribute to neoplastic transformation. The present study aimed to investigate the involvement of both the receptorial and the mitochondrial pathways of apoptosis in normal endometrium and in endometrial carcinoma, by measuring caspase-3 and caspase-8 activities and cytosolic cytochrome c levels. Twelve endometrial carcinomas and nine normal endometrial specimens (four in mild proliferative phase, five in late secretory phase) were included in this study. Cytosolic fractions, obtained by differential centrifugation of tissue homogenates, were analyzed for caspase-3 and caspase-8 activities, as well as for cytochrome c content. Caspase-8 activity in normal secretory phase endometrium was higher than that in the proliferative phase and in the endometrial carcinoma. Moreover, higher cytochrome c levels were detected in endometrial carcinoma with respect to normal secretive endometrium. No significant differences were found in caspase-3 activity between normal and pathologic endometrium. The results obtained suggest that in normal endometrium, apoptosis takes place through the activation of both receptorial and mitochondrial pathways. Defects in both these pathways may contribute to the development of endometrial carcinoma.